2013
DOI: 10.3892/mmr.2013.1668
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 induces mesenchymal stem cells to differentiate into tenocytes through the MAPK pathway

Abstract: Mesenchymal stem cells (MSCs) differentiate into numerous different cell types and thus have therapeutic potential for tissue engineering, anti‑inflammatory and immunomodulatory purposes. FGF2 may affect the biological behavior of MSCs. MSCs were transduced with either adenovirus‑null vector/green fluorescent protein (GFP) or a vector encoding for the overexpression of FGF2/GFP. The expression of FGF2 was demonstrated to be significantly higher in MSC (FGF2) compared with MSC (vector) by qPCR and western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…In our study, for the AdbFGF group, our results demonstrated that cell proliferation and the expression of SCX and COL1 in the BMSCs was markedly enhanced, indicating a shift of BMSCs towards the more mature state of fibroblast-like cells following the gene transfer of bFGF. Our findings collaborate with the findings of the in vitro model by Cai et al, which suggested that bFGF may be an important regulator of the proliferation and differentiation of BMSCs (33). As regards the ligament fibroblasts, cell proliferation was markedly enhanced, and this was accompanied by the decreased expression of COL1 and COL3.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, for the AdbFGF group, our results demonstrated that cell proliferation and the expression of SCX and COL1 in the BMSCs was markedly enhanced, indicating a shift of BMSCs towards the more mature state of fibroblast-like cells following the gene transfer of bFGF. Our findings collaborate with the findings of the in vitro model by Cai et al, which suggested that bFGF may be an important regulator of the proliferation and differentiation of BMSCs (33). As regards the ligament fibroblasts, cell proliferation was markedly enhanced, and this was accompanied by the decreased expression of COL1 and COL3.…”
Section: Discussionsupporting
confidence: 92%
“…MAPKs include 3 families: extracellular signal-regulated kinases (ERKs), c-Jun N-terminal kinases (JNKs), and p38 MAPK [24]. Many factors are involving in the differentiation of Mesenchymal stem cells via MAPK signaling pathways [25,26]. Previous study has shown that MTA could activate MAPK signaling pathways to promote osteo/odontogenic differentiation of dental pulp cells in vitro [27].…”
Section: Introductionmentioning
confidence: 99%
“…A promising stepwise differentiation approach has also been reported using TGF-β1 followed by connective tissue growth factor (CTGF) [54]. Growth factors are commonly delivered as culture medium supplements, but, e.g., FGF-2-transduced MSCs have been used as well [89]. Further tenogenic differentiation approaches based on genetic modifications include the forced expression of the tenogenic transcription factors scleraxis [10,152] 79,81,87], both being used based on evidence that physical cues such as scaffold anisotropy and stiffness direct MSC fate.…”
Section: In Vitro Evidencementioning
confidence: 99%
“…To understand if physiological stimuli could promote the same distinct tenogenic phenotype as artificial TGF-β concentrations, it would be helpful to gain further insight into the downstream signaling networks and their possible interfaces. So far, however, tenogenic signaling has mainly been investigated following growth factor stimulation [67, 82,89,90]. Only few studies have attempted to elucidate the signaling pathways activated in MSC in response to mechanical load or scaffold topographical cues, focusing on the role of rho/ ROCK [154,155].…”
Section: In Vitro Evidencementioning
confidence: 99%